Neither Humans nor Rights: Some Notes on the Double Negation of Black Life in Brazil (2014)
This article examines the challenges of conceptualizing Black existence within the realm of what has been defined as civil society. Rather than entering the Afro-pessimism versus Afro-optimism debate, its aim is to provide ethnographic material to further an understanding of the (im)possibilities for redressing Black injury from racialized categories such as law, justice, and humanity. How might we understand mourning and grieving when the racial alterity of the Black subject positions "it" outside the domains of citizenship and humanity? This double negation-neither human nor citizen-is the basis from which the article provides a critique of the racial terror perpetrated by police-linked death squads in Sao Paulo, Brazil.